Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Photon echoes from (In,Ga)As quantum dots embedded in a Tamm-plasmon microcavity - Salewski, M.; Poltavtsev, S. V.; Kapitonov, Yu. V.; Vondran, J.; Yakovlev, D. R.; Schneider, C.; Kamp, M.; Höfling, S.; Oulton, R.; Akimov, I. A.; Kavokin, A. V.; Bayer, M. (Physical Review B)
We report on the coherent optical response from an ensemble of (In,Ga)As quantum dots (QDs) embedded in a planar Tamm-plasmon microcavity with a quality factor of approximately 100. Significant enhancement of the light-matter interaction is demonstrated under selective laser excitation of those quantum dots which are in resonance with the cavity mode. The enhancement is manifested through Rabi oscillations of the photon echo, demonstrating coherent control of excitons with picosecond pulses at intensity levels more than an order of magnitude smaller as compared with bare quantum dots. The decay of the photon echo transients is weakly changed by the resonator, indicating a small decrease of the coherence time T2 which we attribute to the interaction with the electron plasma in the metal layer located close (40 nm) to the QD layer. Simultaneously we see a reduction of the population lifetime T1, inferred from the stimulated photon echo, due to an enhancement of the spontaneous emission by a factor of 2, which is attributed to the Purcell effect, while nonradiative processes are negligible, as confirmed from time-resolved photoluminescence.

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Solving the Bethe-Salpeter equation for the second-harmonic generation in Zn chalcogenides - Riefer, A.; Schmidt, Wolf Gero (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Vortex-vortex control in exciton-polariton condensates - Ma, Xuekai; Schumacher, Stefan (Physical Review B)

Anisotropic excitons and their contributions to shift current transients in bulk GaAs - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Physical Review B)